Introducing the English Vocabulary and Its Pronunciation to Young Learners Through Community Service Training - Ninsiana, Widhiya; Rosidah, Rosidah; Siregar, Syareni; Deiniatur, Much; Suprihatin, Yeni; Septiyana, Linda; Huda, Miftachul (DEDIKASI: Jurnal Pengabdian Masyarakat, 2024)
This community service was initiated by the English Teaching (Tadris) IAIN Metro lecturer and the student service team (KPM) conducted at TPA REKA. This community service's objective is to introduce English as a second language to children based on their age and needs. TPR method was used to cope with the students' improvement in learning English vocabulary. The results revealed that TPR method implementation for learning English by TPA children has enormous potential for helping students to master the language. The use of TPR method in teaching the early childhood learning benefits children as it helps them to immediately understand the target language or English, allows them to learn with meaningful words and phrases in their contexts, learning becomes more fun for children as they are directly involved in the created situations, stimulates them to learn, which enables their kinesthetics develop